2012
DOI: 10.1007/s10856-012-4592-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of amphiphilic [PEO(PCL)2] triarm star-shaped block copolymers: a promising system for in cell delivery

Abstract: The paper reports on a simple method of synthesizing [PEO(PCL)(2)] triarm star-shaped copolymers by a combination of Michael-addition type reaction and ring-opening polymerization. A Michael-addition reaction yielded a PEO end-capped by two hydroxyl groups-a [PEO(OH)(2)] macroinitiator-which was used for sequential building of PCL blocks. The macroinitiator and copolymers were analyzed by FTIR, (1)H NMR spectroscopy and SEC. The self-assembly behavior of the copolymers in aqueous media was studied by UV-Vis sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…[50] The degradation study showed that 3-arm star-shaped PCL/PEG block copolymers with shorter PCL block length degraded faster. The coreshell micelle sizes fluctuated during the initial degradation period and then increased slightly before finally dropping off.…”
Section: Star-shape Block Copolymers and Their Self-assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…[50] The degradation study showed that 3-arm star-shaped PCL/PEG block copolymers with shorter PCL block length degraded faster. The coreshell micelle sizes fluctuated during the initial degradation period and then increased slightly before finally dropping off.…”
Section: Star-shape Block Copolymers and Their Self-assembliesmentioning
confidence: 99%
“…50] With the fast evolution of polymerization techniques, several synthetic strategies have been reported for the effective synthesis of PCL based star-The obtained 3-arm star-shaped PCL/PEG block copolymers can form micelles by self-assembly without contact with any organic solvent. The micelle properties as investigated by size distribution, zeta potential, and TEM visualization of the micelles indicated that the micelles are homogeneous and stable.…”
mentioning
confidence: 99%
“…Recently Y-shaped three-armed block copolymers with one hydrophilic head and two hydrophobic tails have been receiving a great attention (Li et al, 2013;Wang et al, 2012aWang et al, , 2010Petrova et al, 2012;Maglio et al, 2011). Compared with their linear counterparts, triarm copolymers are characterized with smaller hydrodynamic volume and radius of gyration, and lower melt and solution viscosities (Lapienis, 2009;Sanda et al, 2002;Lele and Leroux, 2002;Joziass et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Star-shaped block copolymers consisting of at least three linear polymeric arms with a radial arrangement around a central molecular fragment (core) 8,9 are usually prepared by the "arm-rst" or "core-rst" methods. The "arm-rst" approach involves the construction of polymer arms on a macroinitiator that contains a precise number of reactive sites.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 These micellar systems are of great interest for medical uses such as the construction of micellar drug delivery systems. 9,[15][16][17][18][19] Signicant differences in the physicochemical properties of star-shaped copolymers compared with their linear analogues can be observed, such as smaller hydrodynamic volume and, radius of gyration and low melt and solution viscosities, which are benecial to drug loading and delivery. [20][21][22][23][24] It has been shown that linear amphiphilic copolymers have limited applications in drug delivery because they suffer from an initial burst release effect.…”
Section: Introductionmentioning
confidence: 99%